Răspuns:
Explicație pas cu pas:
a) (x-1)²-(2x-1)²-6=2-(5-x)-3x(x+1)*23
x²-2x+1-(4x²-4x+1)-6=2-5+x-23*3x(x+1)
x²-2x+1-4x²+4x-1-6=-3+x-69x(x+1)
-2x²+2x-6=-3+x-69x²-69x
-2x²+69x²+2x=-3+6-68x
67x²+2x+68x=3
67x²+70x=3 ceva cred ca e gresit aici.. poate acel *23 de la final
b) (3x-1)²-5(2x+1)²+(6x-3)(2x+1)=(x-1)²+16
9x²-6x+1-5(4x²+4x+1)+(12x²+6x-6x-3)=x²-2x+1+16
9x²-6x+1-20x²-20x-5+12x²-3=x²-2x+17
grupam termenii
(9x²-20x²+12x²)+ (-6x-20x) +1-5-3 = x²-2x+17
x²-26x-7=x²-2x+17
-26x+2x=17+7
-24x=24
x=-24/24
x=-1